Lifelong Bilingualism Functions as an Alternative Intervention for Cognitive Reserve Against Alzheimer's Disease - Liu, Haiqing; Wu, Longhuo (Frontiers in Psychiatry, 2021)
Bilingualism has been reported to significantly delay the onset of dementia and plays an important role in the management of Alzheimer's disease (AD), a condition inducing impairment in the brain network and cognitive decline. Cognitive reserve is associated with the adaptive maintenance of neural functions by protecting against neuropathology. Bilingualism acts as a beneficial environmental factor contributing to cognitive reserve, although some potential confounding variables still need further elucidation. In this article, the relationship between bilingualism and cognitive reserve is discussed, interpreting the advantage of bilingualism in protecting against cognitive decline. In addition, the possible brain and biochemical mechanisms, supporting the advantageous effects of bilingualism in delaying the onset of dementia, involved in bilingualism are reviewed. Effectively, bilingualism can be considered as a pharmacological intervention with no side effects. However, the investigation of the pharmacological parameters of bilingualism is still at an early stage.